Multi-object tracking in MRI-guided radiotherapy using the tracking-learning-detection framework. (September 2019) - Dhont, Jennifer; Vandemeulebroucke, Jef; Cusumano, Davide; Boldrini, Luca; Cellini, Francesco; Valentini, Vincenzo; Verellen, Dirk
Abstract: The application of the tracking-learning-detection (TLD) framework; a performant tracking algorithm for real-life objects in CCD video, was evaluated and successfully optimized for tracking anatomical structures in low-quality 2D cine-MRI acquired during MRI-guided radiotherapy. Sub-pixel tracking accuracy and >95% precision and recall was achieved despite significant deformations and periodical disappearance.